Apprentissage par la lecture en milieu défavorisé: stratégies d’adolescents ayant une faible performance à l’activité - Cartier, Sylvie; Chouinard, Roch; Contant, Hélène (Canadian Journal of Education/Revue canadienne de l'éducation, 2011)
This study aims to understand the involvement of adolescents with poor performance in an activity based on learning through reading in disadvantaged areas. To that end, cognitive and self-learning strategies that these students reported having used during an activity and those used by their peers with better performance were compared. The results generally show that students' strategies vary according to the course and those with poor performance do not use strategies supporting knowledge acquisition as frequently as those with better performance (elaboration in geography and repetition in history).